Product assurance in agile space systems development - Isomäki, Minna (fi=Turun yliopisto|en=University of Turku|, 2015)
Product assurance is an essential part of product development process if developers want to ensure that final product is safe and reliable. Product assurance can be supported with risk management and with different failure analysis methods. Product assurance is emphasized in system development process of mission critical systems. The product assurance process in systems of this kind requires extra attention. In this thesis, mission critical systems are space systems and the product assurance process of these systems is presented with help of space standards. The product assurance process can be supported with agile development because agile emphasizes transparency of the process and fast response to changes. Even if the development process of space systems is highly standardized and reminds waterfall model, it is still possible to adapt agile development in space systems development. This thesis aims to support the product assurance process of space systems with agile development so that the final product would be as safe and reliable as possible. The main purpose of this thesis is to examine how well product assurance is performed in Finnish space organizations and how product assurance tasks and activities can be supported with agile development. The research part of this thesis is performed in survey form.

Tuotevarmennus on oleellinen osa tuotekehitysprosessia kun halutaan varmistua siitä, että lopputuote on turvallinen ja luotettava. Tuotevarmuutta voidaan tukea erityisesti riskienhallinalla ja erilaisilla virheiden analysointimenetelmillä. Tuotevarmennuksen merkitys on korostunut tehtäväkriittisten systeemien tuotekehityksessä, koska systeemien toiminta ja mahdollisesti pitkä käyttöikä vaativat sen, että systeemi toimii alusta alkaen niin kuin on tarkoitettu. Tässä diplomityössä tehtäväkriittisiksi systeemeiksi on valittu avaruusalan systeemit ja niiden tuotevarmistukseen tutustutaan avarustandardiston avulla. Ketterän kehityksen avulla voidaan tuotteen kehitysprosessia tehostaa sillä ketteryys painottaa etenkin prosessin läpinäkyvyyttä ja nopeampaa reagointia muutoksiin. Vaikka avaruussyteemien kehitysprosessi on vahvasti standardisoitu ja muistuttaa hyvin paljon vesiputousmallia, on ketteryyttä kuitenkin mahdollista soveltaa osana avaruusprojektia. Tässä työssä avaruussyteemien tuotevarmuusprosessia pyritään tehostamaan ketteryyden avulla niin, että lopputuote olisi mahdollisimman turvallinen. Tämän diplomityön tarkoituksena on selvittää miten hyvin tuotevarmuus on toteutettu suomalaisissa avaruusalan yrityksissä ja miten tuotevarmuuden työtehtäviä ja aktiviteetteja voitaisiin tukea ketterien menetelmien avulla. Tässä työssä tutkimus on suoritettu kyselytutkimuksen muodossa.